Chemical Composition and Inhibitory Effect of the Essential Oil from Lippia Citriodora Irrigated by Wastewater on the Alkaline Corrosion of Aluminum - Bensabah,F (2014)
The objective of this study is the valorization of the essential oil (EO) of Lippia citriodora irrigated by urban wastewater from the city of Settat-Morocco. We have tested it as a corrosion inhibitor of aluminum in 0.1 M Na2CO3 using polarization method, weight loss, and EIS measurements. The inhibition efficiency of lippia citriodora oil was calculated and compared. We found good agreement between the referred methods. The results obtained revealed that the tested inhibitor reduces differently the kinetic of the corrosion process of aluminum. Its efficiency increases with the concentration and attained 90.33% at 1800 ppm. The effect of temperature on the corrosion behaviour of aluminum in 0.1 M Na2CO3 was also studied in the range 283 K and 313 K. The thermodynamic data of activation were determined. The analysis of Lippia citriodora oil, obtained by hydro-distillation, using gas chromatography (GC), showed that the major components are neral 13.85%, geranial 14.06% and limonene 28.32%.